National health insurance in the United States and Canada : race, territory, and the roots of difference - Boychuk, Gerard William, 1967- (American governance and public policy., 2008)
After World War II, the United States and Canada, two countries that were very similar in many ways, struck out on radically divergent paths to public health insurance. Canada developed a universal single-payer system of national health care, while the United States opted for a dual system that combines public health insurance for low-income and senior residents with private, primarily employer-provided health insuranceor no insurancefor everyone else. In National Health Insurance in the United States and Canada, Gerard W. Boychuk probes the historical development of health care in each coun.